Padrão de consumo e comportamentos relacionados à dependência ao etanol em ratos adolescentes e adultos : influência do estresse neonatal e do sexo - (:unkn) unknown (Universidade Estadual de Goiás, 2018)
Exposure to stress in early life can contribute differentially to consumption and behaviors related to ethanol addiction. However, there is no consensus in the literature whether such differences are influenced by sex and age. Thus, this study investigated the effects of exposure to maternal separation on consumption and conditioned place preference (CPP) to ethanol in both, male and female, adolescent and adult rats. Pregnant Wistar rats (n = 32) were divided into three experimental groups: control, short-term and long-term maternal separation. Separated rat pups were kept apart from their dams once a day from postnatal day (PND) 2 to 10 during 15 and 180 minutes, respectively. Control rat pups were not manipulated during PND 2 to PND 21, except when their cages were cleaned. At the age of PND 28 (adolescence), half of the litter of each group were evaluated in the elevated plus-maze, conditioned place preference (CPP) and voluntary ethanol consumption in a free-choice tests. The other half of the litter was evaluated in the same tests, but in adulthood, that is, from 70th postnatal day. There was no difference in conventional parameters of anxiety between the control, short-term and long-term maternal separation groups for both adolescents and adults, male and female rats. Adolescent rats of both sexes also showed no differences between groups. Adolescent males in the long-term maternal separation group consumed more the 4% ethanol solution than the rats from the control group. On the other hand, the total ethanol intake by adult males from the long-term maternal separation group was higher when compared to the other groups. In addition, these animals consumed more the 8% ethanol solution than other rats from control and short-term maternal separation groups. Total ethanol consumption by adult females that were separated from their dams for both brief and prolonged periods was also higher when compared to the control. CPP was detected in adolescent animals of both sexes from the long-term maternal separation group at a dose of 1.0 g/kg. In adulthood, the doses 0.5 g/kg and 1.0 g/kg ethanol induced CPP in male rats from both short and long-term maternal separation groups, respectively. Conversely, induction of CPP at doses of 0.5 g/kg and 1.0 g/kg ethanol was not detected in adult females. Taken together, these results showed that exposure to maternal separation, either brief or prolonged, did not induce behavioral symptoms of anxiety in animals. However, the protocol of prolonged maternal separation increased the reinforcing effects of ethanol in the models of consumption and PCL, determining differences in behaviors related to dependence between adolescent and adult, male and female rats.
Keywords: Labirinto em cruz elevado; Consumo voluntário de etanol; Preferência condicionada por lugar; Estresse neonatal; Elevated plus maze; Voluntary consumption of ethanol; Conditioned place preference; Neonatal stress; CIENCIAS BIOLOGICAS::FISIOLOGIA; CIENCIAS BIOLOGICAS::FARMACOLOGIA